Restorative Rehabilitation of Tooth Wear: A Clinical Case Report - Khare, Anshika; Dayma, Ashwini (Journal of Orofacial Research, 2018)
Tooth wear is a grave trouble, which affects oral cavity attainments by its predation, apprehension, mastication, and ingestion of food. Management of tooth wear is always a big confront to dentist to restore its normal anatomical and functional values. This article presents a case report on restorative rehabilitation of tooth wear by private dental practitioner.